Advances on Post-translational Modifications Involved in Seed Germination - Yu, Feng; Li, Ming; He, Dongli; Yang, Pingfang (Frontiers in Plant Science, 2021)
Seed germination and subsequent seedling establishment are important developmental processes that undergo extremely complex changes of physiological status and are precisely regulated at transcriptional and translational levels. Phytohormones including abscisic acid (ABA) and gibberellin (GA) are the critical signaling molecules that modulate the alteration from relative quiescent to a highly active state in seeds. Transcription factors such as ABA insensitive5 (ABI5) and DELLA domain-containing proteins play the central roles in response to ABA and GA, respectively, which antagonize each other during seed germination. Recent investigations have demonstrated that the regulations at translational and post-translational levels, especially post-translational modifications (PTMs), play a decisive role in seed germination. Specifically, phosphorylation and ubiquitination were shown to be involved in regulating the function of ABI5. In this review, we summarized the latest advancement on the function of PTMs involved in the regulation of seed germination, in which the PTMs for ABI5 and DELLA containing proteins play the key roles. Meanwhile, the studies on PTMs-based proteomics during seed germination and the crosstalk of different PTMs are also discussed. Hopefully, it will facilitate in obtaining a comprehensive understanding of the physiological functions of different PTMs in seed germination.